2015
DOI: 10.1109/jestpe.2015.2439296
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid PWM-Based DC-Link Voltage Balancing Algorithm for a Three-Level NPC DC/AC Traction Inverter Drive

Abstract: This paper presents a hybrid pulse-width modulation (H-PWM) technique, for a 3-level neutral point clamped (NPC) electric vehicle (EV) traction inverter drive. The proposed strategy depicts the advantages of both classic space-vector pulsewidth modulations (SV-PWM) as well as carrier-based PWM.The duty-cycles for the traction inverter switches are calculated using carrier-based PWM, to reduce the computational time and control complexity of the system. The redundancies of the switching states are then used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…23, presents a comparison between the I cat spectra for both solutions with limits recalculated for 4 and 8 drives operating in parallel in one EMU. It can be observed that changing the solution from 'SOL1' into 'SOL2' maintains the operating point (M1,f fal -unchanged), but the fulfils limits recalculated even for the 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23, presents a comparison between the I cat spectra for both solutions with limits recalculated for 4 and 8 drives operating in parallel in one EMU. It can be observed that changing the solution from 'SOL1' into 'SOL2' maintains the operating point (M1,f fal -unchanged), but the fulfils limits recalculated even for the 8 …”
Section: Discussionmentioning
confidence: 99%
“…The techniques of neutral point voltage balancing in multilevel inverters are described in literature for both PWM [8] and SHE [7] modulations. However, this article does not present balancing techniques due to the fact that their influence on generated harmonics is outside of the scope of this paper.…”
Section: Influence Of Non-balanced Neutral Point Voltage In 3-level Vsimentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that [8,9] state that the modulation scheme used here cannot work properly with dynamic loads such as motors, because the converter would not be able to keep the capacitor-voltage fluctuations low, leading to a system instability. This modulation is implemented here together with the VBC to drive a PMSM, demonstrating the feasibility of the proposed controller for motor-drive applications.…”
Section: Introductionmentioning
confidence: 99%
“…With space vector based hybrid PWM techniques is possible to reduce the current ripple [2]. Other way could be using a hybrid method combining both the generated-carrier-based PWM and the space-vector-based hybrid PWM [3].…”
Section: Introductionmentioning
confidence: 99%